Underlying Host Risk Factors for Nontuberculous Mycobacterial Lung Disease - Chan, Edward D.; Iseman, Michael D. (Seminars in Respiratory and Critical Care Medicine, 2013)
Nontuberculous mycobacteria (NTM) are environmental microbes that cause a variety of human diseases, particularly chronic lung infections. Despite the fact that NTM are widespread in the environment, relatively few people develop NTM lung disease, suggesting intrinsic vulnerability in some individuals. This paper reviews the evidence that underlying disorders predispose to NTM lung disease, in particular primary conditions that result in bronchiectasis, chronic obstructive pulmonary disease, α-1-antitrypsin anomalies, pneumoconiosis, pulmonary alveolar proteinosis, and frank immunosuppressive states such as that associated with the use of anti–tumor necrosis factor-α biologics, posttransplantation immunosuppression, and HIV infection. Over the past several decades, NTM lung disease has been increasingly identified in postmenopausal women with slender body habitus. Thus we will also review the clinical and experimental evidence which supports the observation that such individuals are predisposed to NTM lung disease.
Keywords: Marfan syndrome; environmental mycobacteria; bronchiectasis; pectus excavatum; scoliosis; nontuberculous mycobacteria